SOLIDARITAS SOSIAL MUSLIM MINORITAS DI INGGRIS DALAM FILM BLINDED BY THE LIGHT - Rakhmadi, Herlambang Dwi Prasetyo (Universitas Cokroaminoto Yogyakarta, 2024)
The purpose of this research is first, to examine in depth the function of film as a communication medium that describes the values, norms, culture, and beliefs of society. Second, to find out the challenges and obstacles as well as the solidarity experienced by minority Muslims in the film Blinded by The Light. This qualitative analysis study is focused on the film Blinded by The Light by Gurinder Chada which was released on 27 August 2019 using cultural studies aimed at observing the culture in this film and secondary data obtained through articles, news and websites. This film tells about the life of Javed as the main character with his family who are immigrants from Pakistan and live in Luton, England. The results of this study found the challenges and obstacles received by Javed, his family, community, and other minorities from non-physical to physical forms internally Javed experienced an identity crisis and family problems, namely his authoritarian and old-fashioned father and externally, namely discrimination in the form of threats to violence committed both individually and in groups as perpetrated by the National Front. Social solidarity was built by Javed and his group both internally, namely with fellow immigrants from Pakistan, and externally with British people who supported their cause and with groups that opposed the National Front, namely the Anti-National Front group. This social solidarity is aimed at seeking justice and equality which they find difficult to obtain as a minority.